The Use of Soft Madurese Language (Engghi-Phunten) on Children's Moral Values Development - Syafitri, Rini; Musayyadah, Musayyadah (PROGRAM STUDI MAGISTER PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD) FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2024)
Moral values are a relationship between good and bad values that are carried out to guide children's lives. The importance of moral values in children is really needed when children are in their golden age. The use of the Madurese enggi-bunten language is a strong tool in the need for good values. Ingrained in the child. This research was used to look at the moral development of children aged 5-6 years through the use of the Madurese enggi-bunten language at the Al-Azhar Kowel Pamekasan Kindergarten. By using the habituation learning method using Madurese, the research method used was a descriptive qualitative research method with data collection. used are observation, interviews and documentation. The results show that the use of Madurese enggi-bunten language at Kindergarten-Al Azhar Kowel Pamekasan can increase children's moral values and knowledge of Madurese vocabulary, so that children can distinguish good language use when communicating with people around them, whether when communicating with teachers, friends, or parents are accompanied by good and polite actions.